Andropause in Indian Men: a Preliminary Cross-Sectional Study - Goel, Apul; Sinha, Rahul Janak; Dalela, Divakar; Sankhwar, Satyanarain; Singh, Vishwajeet (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The purpose of this study was to determine the frequency of androgen decline in the aging male (ADAM) in a group of Indian men working in the health sector. Materials and Methods: A free medical health checkup camp was organized for the male workers aged between 40 and 60 years employed in surgical departments of our hospital. Of 180 listed male workers, 170 attended this camp and 157 eligible men participated in the study. After clinical history and systemic inquiry, the participants were requested to complete the Saint Louis Universityâ€™s ADAM questionnaire, and their serum levels of free and total testosterone were measured. Results: Symptomatic andropause was found in 106 men (67.5%) on the basis of their responses to the questionnaire, of whom 41 (38.7%) had low serum free testosterone levels and 32 (30.2%) had low serum levels of total testosterone. Fifty-one men were asymptomatic according to the questionnaire and in this group, 11 (21.6%) had low serum free testosterone levels and 6 (11.8%) of these had low total testosterone levels. The frequency of andropause was 33.1% on the basis of low serum free testosterone levels and it was 26.1% when both symptoms and low serum free testosterone levels were taken into account. Conclusion: In our study, the high frequency of symptoms related to ADAM was unusual. This might be due to the nature of the questionnaire itself. Serum free testosterone measurement may be a better single test for diagnosis of hypogonadism than serum total testosterone measurement.